A pan-cetacean MHC amplicon sequencing panel developed and evaluated in combination with genome assemblies - Heimeier, Dorothea; Garland, Ellen; Carroll, Emma; Eichenberger, Franca; Garrigue, Claire; Vella, Adriana; Baker, Scott (Zenodo, 2024)
The major histocompatibility complex (MHC) is a highly polymorphic gene family that is crucial in immunity, and its diversity can be effectively used as a fitness marker for populations. Despite this, MHC remains poorly characterised in non-model species (e.g., cetaceans: whales, dolphins and porpoises) as high gene copy number variation, especially in the fast-evolving class I region, makes analyses of genomic sequences difficult. To date, only small sections of class I and IIa genes have been used to assess functional diversity in cetacean populations. Here, we undertook a systematic characterisation of the MHC class I and IIa regions in available cetacean genomes. We extracted full-length gene sequences to design pan-cetacean primers that amplified the complete exon2 from MHC class I and IIa genes in one combined sequencing panel. We validated this panel in 19 cetacean species and described 354 alleles for both classes. Furthermore, we identified likely assembly artefacts for many MHC class I assemblies based on the presence of class I genes in the amplicon data compared to missing genes from genomes. Finally, we investigated MHC diversity using the panel in 25 humpback and 30 southern right whales, including four paternity trios for humpback whales. This revealed copy-number variable class I haplotypes in humpback whales, which is likely a common phenomenon across cetaceans. These MHC alleles will form the basis for a cetacean branch of the Immuno-Polymorphism Database (IPD-MHC), a curated resource intended to aid in the systematic compilation of MHC alleles across several species, to support conservation initiatives. Funding provided by: Royal Society Crossref Funder Registry ID: https://ror.org/03wnrjx87 Award Number: RGF\R1\181014 A total of 85 tissue samples were taken from individual animals across several cetacean species. The type of tissue were either from strandings or biopsies. Stranding samples in New Zealand were taken by the Department of Conservation New Zealand and sent to the New Zealand ...